Observation of Red Panda (Ailurus fulgens) in Choyatar, Ilam, East Nepal - Chalise, M. K. (Journal of Natural History Museum, 2009)
A short survey of Red Panda was conducted in Choyatar Community forest of Ilam district, East Nepal. A pair of pandas was observed and behaviors were recorded. It is significant in Nepalese perspective that a protected species was recorded outside the protected area and relatively better natural habitat. Keywords: Community; Behavior; Protected species; Natural habitat. Journal of Natural History Museum Vol. 24, 2009 Page: 96-102